Pemberdayaan Ekonomi Terhadap Perempuan Melalui Keterampilan Menyulam di PKBM Kenanga Desa Margahurip Kecamatan Banjaran Kabupaten Bandung - Hendi Suhendraya Muhtar; Revita Yanuarsari (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Community empowerment is a process of development in which the community initiates to initiate the process of social activities to improve the situation and conditions themselves. Community empowerment can only occur when the citizens participate. Development and empowerment of society today, has strengthened awareness in the midst of society even can be said as alternative development that enable able to cultivate society passion to lift degree especially in economic independence. Economic empowerment of women through embroidering skills in PKBM Kenanga Margahurip Village, Banjaran District, Bandung Regency has become a tangible manifestation in improving the family economy, so that independence can be felt by most of the trainees. Community empowerment, implemented in PKBM KENANGA, run effectively and efficiently so as to produce a positive outcome, that is able to make women especially in improving the family economy.